Transcriptomic profile assessment for preeclampsia prediction and early diagnostics - A. V. Melnik; V. E. Solovyova; Yu. O. Yatsenko; A. E. Filippova; E. G. Asryan; T. Е. Seitumerov; E. R. Myshak; Yu. A. Chernysheva; S. A. Ziyadinova; V. O. Kononenko; M. R. Kadyrova; A. A. Denisenko; et al. (Акушерство, гинекология и репродукция)
Aim: to develop a model for predicting preeclampsia (PE) based on the clinically most significant differentially expressed plasma microRNAs.Materials and Methods. A prospective observational comparative study was conducted with 62 women, divided into two parallel groups: 32 patients with PE and 30 clinically healthy women with uncomplicated pregnancy. Transcriptomic analysis was performed to identify differentially expressed blood plasma microRNAs using next generation sequencing (NGS).Results. Calculation of risk ratios for PE development allowed to identify 14 plasma microRNAs that influence the development of PE pathology. PE-associated microRNAs hsa-miR-103a-3p, hsa-miR-451a and hsa-miR-516a-5p have a high diagnostic value when combined to assess their blood plasma expression level in early pregnancy stages.Conclusion. The developed prognostic model can be applied to pregnant women at risk for PE development, which may further reduce obstetric complications and improve perinatal outcomes.